Implementasi Sistem Kontrol dan Monitoring PH dan Suhu Air Pada Sistem Smart Aquaponic Berbasis Mikrokontroler Esp32 - Syaffa Widyadari; Raden Muh Sultoni (Universitas Dirgantara Marsekal Suryadarma, 2026)
Aquaponic systems represent a sustainable agricultural approach that integrates fish cultivation and plant production within a recirculating water ecosystem. The stability of water quality parameters, particularly pH and temperature, is essential for maintaining system productivity. Manual monitoring and control are often inefficient and may lead to parameter fluctuations. This study aims to design and implement an Internet of Things (IoT)-based monitoring and control system for water pH and temperature using an ESP32 microcontroller. The system utilizes a pH 4502C sensor and a DS18B20 temperature sensor to monitor water conditions in real time. Data are processed by the ESP32 and transmitted via the internet, supported by Telegram-based notifications and automatic control using relay modules to maintain pH within 6.5–7.5 and temperature within 24–28°C.System testing was conducted over three days with data collection every two hours. Sensor validation was performed by comparing sensor readings with calibrated digital measuring instruments as reference standards, followed by the calculation of relative error and accuracy percentages. The results show that the pH sensor achieved an accuracy of 92–95% with an average error of ±0.3 pH, while the temperature sensor reached an accuracy of 98–99% with an average error of ±0.2°C. The system demonstrated a response time of less than 5 seconds and a 100% data transmission success rate. The integration of IoT monitoring and ESP32-based automatic control validated within a Recirculating Aquaculture System (RAS) environment constitutes the main contribution of this study.